A Critique of the Research on Latin American Thought - Pérez Jiménez, César Augusto (2018)
This work presents a critique of the praxis of research on Latin American thought from the problematization of the territorial and the human in a historical-epistemological perspective. This critique, of argumentative nature, derives from the understanding of the territory as a place of enunciation of the interstices created between the conquest and the colony to guide the study of the nominality of America as part of the modern-colonial geopolitics. It examines how, from the designation of the territory, a civilizing project was erected that marred the authentic and original development of the initial cultures as part of the imposition of economic and political textualities located in the constitution of the liberal-enlightened state, which facilitated the production of a civilizing, pedagogical project oriented towards the subalternization of native peoples. Finally, it establishes a space to discuss the requirements of a methodology for the investigation of Latin American thought as a preamble to the search for meanings in the liberating praxis of research on Latin American thought.